Factors influencing engagement in an online support group for family caregivers of individuals with advanced cancer. Issue 3 (3rd May 2020) - Washington, Karla T.; Oliver, Debra Parker; Benson, Jacquelyn J.; Rolbiecki, Abigail J.; Jorgensen, Lucas A.; Cruz-Oliver, Dulce M.; Demiris, George
Abstract: Objective: To explore factors that influenced engagement in an online support group (OSG) for family caregivers of hospice patients with cancer. Design: Secondary qualitative data analysis. Sample: 58 family caregivers of hospice patients with advanced cancer. Methods: Template analysis of individual family caregiver interviews. Findings: Emotional isolation and caregiving downtime positively influenced engagement, while reluctance to share personal information, a short timeframe of participation in the OSG, and caregiving commitments were negatively influential. While the group facilitation and secure privacy settings of the OSG were viewed positively, reactions to the OSG platform and group tone were mixed. Information on pain and the dying process was found to be particularly engaging. Practice implications: Providers offering OSGs for family caregivers should maximize factors that promote meaningful member engagement, responding to changes in activity and tone over time.